Genomic amplification patterns of human telomerase RNA gene and C-MYC in liquid-based cytological specimens used for the detection of high-grade cervical intraepithelial neoplasia - Chen Shaomin; Yang Ziyan; Zhang Yun; Qiao Yunbo; Cui Baoxia; Zhang Youzhong; Kong Beihua (BMC, 2012)
Abstract Background The amplification of oncogenes initiated by high-risk human papillomavirus (HPV) infection is an early event in cervical carcinogenesis and can be used for cervical lesion diagnosis. We measured the genomic amplification rates and the patterns of human telomerase RNA gene (TERC) and C-MYC in the liquid-based cytological specimens to evaluate the diagnostic characteristics for the detection of high-grade cervical lesions. Methods Two hundred and forty-three residual cytological specimens were obtained from outpatients aged 25 to 64 years at Qilu Hospital, Shandong University. The specimens were evaluated by fluorescence in situ hybridization (FISH) using chromosome probes to TERC (3q26) and C-MYC (8q24). All of the patients underwent colposcopic examination and histological evaluation. A Chi-square test was used for categorical data analysis. Results In the normal, cervical intraepithelial neoplasia grade 1 (CIN1), grade 2 (CIN2), grade 3 (CIN3) and squamous cervical cancer (SCC) cases, the TERC positive rates were 9.2%, 17.2%, 76.2%, 100.0% and 100.0%, respectively; the C-MYC positive rates were 20.7%, 31.0%, 71.4%, 81.8% and 100.0%, respectively. The TERC and C-MYC positive rates were higher in the CIN2+ (CIN2, CIN3 and SCC) cases than in the normal and CIN1 cases (p < 0.01). Compared with cytological analysis, the TERC test showed higher sensitivity (90.0% vs. 84.0%) and higher specificity (89.6% vs. 64.3%). The C-MYC test showed lower sensitivity (80.0% vs. 84.0%) and higher specificity (77.7% vs. 64.3%). Using a cut-off value of 5% or more aberrant cells, the TERC test showed the highest combination of sensitivity and specificity. The CIN2+ group showed more high-level TERC gene copy number (GCN) cells than did the normal/CIN1 group (p < 0.05). For C-MYC, no significant difference between the two histological categories was detected (p > 0.05). Conclusions The TERC test is highly sensitive and is therefore suitable for cervical cancer screening. The C-MYC test is not suitable for cancer screening because of its lower sensitivity. The amplification patterns of TERC become more diverse and complex as the severity of cervical diseases increases, whereas for C-MYC, the amplification patterns are similar between the normal/CIN1 and CIN2+ groups. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1308004512669913.